Characterization and Kinetics of Calcium Sulfate Dihydrate Crystallization in the Presence of Trimesic Acid - SAYAN, PERVİZ; POLAT, SEVGİ (WILEY, 2017)
In this study, calcium sulfate dihydrate crystallization was studied within a mixed-suspension, mixed-product-removal-type crystallizer at 65 degrees C and 2.5 pH in pure media and in the presence of trimesic acid. The experiments were performed at different trimesic acid concentrations (250, 1000, and 2500 p.p.m.) through the reaction of calcium carbonate solution with sulfuric acid solution. The crystal size distributions (CSDs) and filtration rates of calcium sulfate dihydrate crystals were measured, and the crystals obtained were also analyzed by thermogravimetric analysis-coupled with Fourier transform infrared-mass spectrometry and scanning electron microscopy. It was determined that the length/width ratio of the crystals obtained in the trimesic acid additive media decreased compared with the crystals obtained in the pure media. Both the filtration rate and the average particle size decreased with an increase in trimesic acid concentration. The kinetics of crystal growth of calcium sulfate dihydrate has been analyzed on the basis of McCabe's Delta L law. It has been found that the growth rate of crystals depends on the particle size, which was specified using Abegg, Stevens, and Larson, Canning and Randolph, two-parameter Mydlarz and Jones, and three-parameter Mydlarz and Jones size-dependent growth models. Results indicated that three-parameter Mydlarz and Jones model ideally fitted for the characterization of the system because it has high relative coefficient and low square deviation. The presence of trimesic acid also led to a decrease in the growth rate of calcium sulfate dihydrate crystals. (C) 2017 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: calcium sulfate dihydrate; trimesic acid; crystallization kinetics; TGA-FTIR-MS; SIMULATED CONDITIONS; L-SORBOSE; GROWTH; DEHYDRATION; NUCLEATION; INHIBITORS; CRYSTALS; ALUMINUM; GYPSUM; IR